1996
DOI: 10.1148/radiology.199.2.8668803
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma: evaluation with biphasic, contrast-enhanced, helical CT.

Abstract: Use of both HAP and PVP contrast-enhanced CT optimizes the evaluation of patients with or at risk for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
159
4
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(174 citation statements)
references
References 14 publications
7
159
4
4
Order By: Relevance
“…Histopathological studies have demonstrated a progressive increase in the arterial supply to nodules evolving toward malignancy, [28][29][30] providing the clues for the clinical diagnosis with imaging techniques. 20,[31][32][33][34][35] To give a solid basis for the noninvasive diagnosis, the EASL panel of experts determined that this pattern must be confirmed by two different imaging techniques in nodules larger than 2 cm. No reference was made to vascularity for nodules between 1 and 2 cm, and it was pointed out that these lesions require histopathological investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological studies have demonstrated a progressive increase in the arterial supply to nodules evolving toward malignancy, [28][29][30] providing the clues for the clinical diagnosis with imaging techniques. 20,[31][32][33][34][35] To give a solid basis for the noninvasive diagnosis, the EASL panel of experts determined that this pattern must be confirmed by two different imaging techniques in nodules larger than 2 cm. No reference was made to vascularity for nodules between 1 and 2 cm, and it was pointed out that these lesions require histopathological investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors greater than 1 cm in size have a sensitivity greater than 90%. 49,[50][51][52][53][54] In general, sensitivity of contrast-enhanced CT (without the triple phase) ranges from 53%to 95%. 34,[47][48][49]51,53,55 A CT scan's specificity in detecting HCC is approximately 94%.…”
Section: Screening Sensitivity and Specificitymentioning
confidence: 99%
“…49,[50][51][52][53][54] In general, sensitivity of contrast-enhanced CT (without the triple phase) ranges from 53%to 95%. 34,[47][48][49]51,53,55 A CT scan's specificity in detecting HCC is approximately 94%. 34,[47][48][49]51,53,55 The gold standard for serological and radiological screening tests for HCC is based on longitudinal follow-up and tissue diagnosis (biopsy, surgical resection, and transplant explant).…”
Section: Screening Sensitivity and Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…HCC nodules were detected by two imaging modalities consisting of US and MDCT. The diagnosis of HCC was confirmed using US-guided fine-needle biopsy specimens or from typical findings observed during MDCT (hyperattenuation area at the hepatic arterial phase, and hypoattenuation at the delayed phase) [17,18]. Of these 364 patients, 67 consecutive patients diagnosed with HCC for the first time were enrolled in this study, and these patients underwent CTAP and CTHA during admission, within 4 weeks following MDCT.…”
Section: Patientsmentioning
confidence: 99%